Pediatric COVID-19 ─ What kind of disease is it? - Salazar,Luís (2022)
Abstract Background: The burden of COVID-19 is reported to be less significant in pediatric patients, with lower morbidity and mortality. Our center secured daily telephone follow-up for pediatric COVID-19 outpatients during the isolation period of the pandemic. The aim of this study was to describe COVID-19 manifestations in the pediatric population. Methods: This was a retrospective cohort study of pediatric COVID-19 patients conducted between March 2020 and September 2021. Pediatric patients with positive SARS-CoV-2 nucleic acid amplification test performed in Emergency Department, hospitalization, or pre-surgery setting in our center, and patients followed in regular appointments in our center with positive SARS-CoV-2 test performed elsewhere were included. Cases of multisystem inflammatory syndrome in children were excluded. Demographic data, medical history, and data regarding disease course and severity were collected. Results: Two hundred and forty-two patients were included, with a median (range) age of 48 (10-144) months. Approximately one third of patients (36.0%) had at least one chronic condition, and 142 had had a prior contact with an infected relative. At diagnosis, the large majority of patients (83.9%) were symptomatic, with fever, cough, rhinorrhea, and nasal congestion as main complaints. A total of 19.8% of patients were initially hospitalized. Among the 194 patients discharged, 22 required reassessment, eight of whom needed hospitalization. Most of these (91.7%) had mild disease or were asymptomatic, while 5.8% fulfilled criteria for moderate disease and 2.5% for severe disease. Two patients required admission to the Intensive Care Unit, one of whom died. Conclusions: In this pediatric cohort, COVID-19 presented mostly as a mild disease, with non-specific and multiple symptoms. The close follow-up conducted at our center enabled a better understanding of the disease and minimizing unnecessary emergency visits and hospitalizations, while maintaining adequate patient follow-up.